Предмет: Алгебра,
автор: Nastyaveremeenko2002
(-5x + 3)(-x+6)=0
x-2/x-6= -1
9x+6/7 + 3= 7x/6
(x-3)(x-4)(x-5)=(x-2)(x-4)(x-5)
Помогите пожалуйста
Ответы
Автор ответа:
0
щас будет 2 часть 5 мин
Приложения:
![](https://files.topotvet.com/i/69c/69ca47e2f41ccbed7e251ec1d0801330.jpg)
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: smatkoevdokia
Предмет: Литература,
автор: ivsirotin2019
Предмет: Математика,
автор: subbotina129338
Предмет: Математика,
автор: mashaivakhnenko